Peterson's Graduate programs in the Physical sciences, Mathematics : (Thomson Peterson's, 2006)
This volume contains more than 3,700 programs of study in 52 disciplines of the physical sciences, mathematics, agricultural sciences, the environment, and natural resources. Features and benefits include: * Informative data profiles for more than 3,700 graduate programs in 52 disciplines with facts and figures on accreditation, faculty, students, degree requirements, application deadlines, expenses, financial support and application contacts. * Nearly 200 two-page In-Depth Descriptions written by the institution give complete details on graduate study. * Advice on the admissions process, financial support, and accreditation and accrediting agencies. * Directories list programs in each volume. * Appendixes list institutional changes since the last edition and abbreviations used in the guide.